Livestock production systems in wetlands of Argentina: assessing transition toward sustainable agroecological systems - Muchiutti, Ayelén Andrea (2025)
The magnitude of the current environmental degradation requires an urgent restructuring of food production systems. In this sense, agroecology is considered a sustainable approach, because it provides tools to guide transition toward sustainable production systems and to meet the Sustainable Development Goals (SDG). Nevertheless, it is imperative to possess evidence regarding the implementation of agroecology and current extent. The goals of this study are to compare two instruments for assessing agroecological transitions, to measure the agroecological performance of extensive livestock systems in slightly disturbed wetlands, identify agroecological elements that differentiate farm categories, and identify relationships among these elements. We evaluated 19 representative extensive livestock production ranches from central-western Argentina. We used the Characterization of Agroecological Transition (CAET) from the Tool for Agroecology Performance Evaluation (TAPE). Moreover, CAET was modified through interaction with ranchers and technicians (Adapted CAET). The results obtained with both tools revealed that the agroecological performance of extensive livestock systems is currently in transition, with an overall average of 56.9%. This suggests that there is a group of farmers implementing agroecological strategies which have the potential to drive the transition to achieve the SDGs. This research provides valuable knowledge for applying agroecology principles in minimally impacted wetlands.